Renaissance papers 2015 - Pearce, Jim (Director of Graduate Studies); Risvold, Ward J. (Renaissance papers, 2016)
Annual volume of the best essays submitted to the Southeastern Renaissance Conference, this year with an emphasis on English drama and the cultural anxieties it expresses.